First Graders in a College Sociology Classroom: A Reflection - Waksler, Frances Chaput (Qualitative Sociology Review, 2012)
Once a year from 1995 until 2008 I offered a sociology class session in which first graders from a local private school joined college undergraduates who were enrolled in my advanced theories course entitled Sociological Studies of Children. The sessions had two goals: to have college students interact with the first graders guided by what we had been learning in class and to introduce first graders to college and to sociology. These joint classes are worthy of further reflection for what they suggest about the potential theoretical, methodological, and practical uses of ideas drawn from the “new sociology of childhood.”This paper is a retrospective description of and reflection on these joint classes. It begins with a presentation of the theoretical background that framed the event. It then details the preparations for the class with the college students; the class itself, including the format and content of lectures and discussions; and the post-visit discussion with the college students. Additional issues described are the influences of the adults (parents) who accompanied the children and some unexpected matters that arose in some of the classes.The first graders’ participation in a college sociology class drew on the ideas of taking children seriously as learners about sociology and recognizing children’s expertise about what it is like to be children. Taking seriously children’s actions, comments, and concerns in non-judgmental ways provides insights into children’s ways, alternative modes of interaction, and new approaches to studying children.